EFEKTIVITAS E-MODUL BERBASIS PENDEKATAN DEDUKTIF PADA MATERI SISTEM EKSKRESI MANUSIA TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Nur Maulani Setyoningtyas; Dyah Astriani; Ahmad Qosyim (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aims to describe the effectiveness of digital modules based on deductive approaches to improve student learning outcomes. There are 15 students from the 2nd grade of SMPN 1 Purwosari academic year of 2020/2021 at even semester that they had been being the subject of the research. This research classified as pre-experimental research; one group pretest-posttest design. The learning was using digital modules through Whatsapp Messenger media for coordination, coordination that occurs six times, including the pretest and posttest giving, as well as student response questionnaires. The response' questionnaire contains the assessment of learners on the use of e-module based on deductive approaches. The results of various research data processing show that the effectiveness of digital modules is fairly good. The N-gain score obtained a moderate category result. Paired Sample T-test obtained a significance level result (effective). While on the response questionnaire score the response was in the very good category. This shows that there is a difference in the test results of students due to the use of digital modules. Based on the results of several tests, it is concluded that digital modules based on deductive approaches are effective for improving the learning outcomes of the subject research.